Herbal medicines used in the treatment of malaria in Budiope county, Uganda - Tabuti, John R.S. (Journal of ethnopharmacology, 2008)
This studywas conducted to document herbal medicines (HMs) used in the treatment of malaria as well as the existing knowledge, attitudes and practices related to malaria recognition, control and treatment in Budiope county, Uganda. Methods: Data was collected using semi-structured interviews, and open- and close-ended questionnaires. Results: The respondents had a good understanding of malaria, and could recognize it and distinguish it from other fever types. They were also aware that malaria was spread by mosquitoes. Malaria prevalence was high, and affected individuals an average of six times a year. Respondents avoided mosquito bites by using mosquito nets, clearing bush around their homesteads, and burning plant parts to generate smoke. They preferred treating malaria using allopathic medicines because, according to them, they lacked the appropriate traditional knowledge necessary to exploit plants for the treatment of malaria. Secondly, allopathic medicines were believed to be superior to HMs in the treatment of malaria. Twenty-seven species were used for the treatment of malaria. The most frequently mentioned were Vernonia amygdalina, Momordica foetida, Zanthoxylum chalybeum, Lantana camara and Mangifera indica. Drugs from these plants were prepared from single species as water extracts and were administered in variable doses over varied time periods.
Keywords: Medicinal plants; Traditional treatments; Ethnobotany; Antimalarial